Resting Ca2+ fluxes protect cells from fast mitochondrial fragmentation, cell stress responses, and immediate transcriptional reprogramming - Caroline Fecher; Annemarie Sodmann; Felicitas Schlott; Juliane Jaepel; Franziska Schmitt; Isabella Lengfelder; Thorsten Bischler; Bernhard Nieswandt; Konstanze F. Winklhofer; Robert Blum (Cellular and Molecular Life Sciences)
Abstract Homeostatic calcium ion (Ca2+) fluxes between the endoplasmic reticulum, cytosol, and extracellular space occur not only in response to cell stimulation but also in unstimulated cells. Using murine astrocytes as a model, we asked whether there is a signaling function of these resting Ca2+ fluxes. The data showed that endoplasmic reticulum (ER) Ca²⁺ depletion, induced by sarcoplasmic/endoplasmic reticulum Ca²⁺-ATPase (SERCA) inhibition, resulted to prolonged Ca²⁺ influx and mitochondrial fragmentation within 10 to 30 min. This mitochondrial fragmentation could be prevented in Ca2+-free medium or by inhibiting store-operated Ca2+ entry (SOCE). Similarly, attenuation of STIM proteins, which are vital ER Ca2+ sensors, protected mitochondrial morphology. On the molecular level, ER Ca2+ depletion, achieved either by removing extracellular Ca2+ or through acute SERCA inhibition, led to changes in gene expression of about 13% and 41% of the transcriptome within an hour, respectively. Transcriptome changes were associated with universal biological processes such as transcription, differentiation, or cell stress. Strong increase in expression was observed for the transcription factor ATF4, which is under control of the kinase PERK (EIF2AK3), a key protein involved in ER stress. Corroborating these findings, PERK was rapidly phosphorylated in Ca2+-free medium or after acute pharmacological inhibition of SOCE. In summary, resting, homeostatic Ca2+ fluxes prevent immediate-early cell stress and transcriptional reprogramming.